2016
DOI: 10.1177/1471301214548522
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic use of dolls for people living with dementia: A critical review of the literature

Abstract: BackgroundThere are a number of therapies currently available to assist health professionals and carers with non-pharmacological treatment for people living with dementia. One such therapy that has been growing in clinical practice is doll therapy. Providing dolls to some people living with dementia has the potential to enhance personal well-being through increased levels of communication and engagement with others. Despite its potential for benefits, the practice is currently under-developed in healthcare lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…To date, 17 studies (see Table ) have been published on DT for older adults with dementia. Since the literature review on this topic by Mitchell, McCormack, and McCance (2016), 6 more recently published studies clearly confirmed that, after DT, people with dementia were more engaged in proposed activities, and more communicative with their caregivers . A reduction in wandering and in the need for neuroleptics has also been demonstrated …”
Section: Introductionmentioning
confidence: 93%
“…To date, 17 studies (see Table ) have been published on DT for older adults with dementia. Since the literature review on this topic by Mitchell, McCormack, and McCance (2016), 6 more recently published studies clearly confirmed that, after DT, people with dementia were more engaged in proposed activities, and more communicative with their caregivers . A reduction in wandering and in the need for neuroleptics has also been demonstrated …”
Section: Introductionmentioning
confidence: 93%
“…Namaste residents are assessed for pain and discomfort, and treated if necessary. The Namaste Care worker offers personal care as meaningful activity alongside individualised interventions, e.g., rummage boxes, or doll therapy if judged appropriate (24). Fluids are offered frequently during Namaste along with high caloric food treats.…”
Section: The Intervention-the Namaste Care Programme (Namaste)mentioning
confidence: 99%
“…Existing pharmacological options in NPS treatment include atypical antipsychotics, benzodiazepines, and other drugs (eg, mood stabilizers), which may, however, increase the risk of cognitive decline, cerebrovascular events, or mortality . Differently, systematic reviews have demonstrated the effectiveness of nonpharmacological treatments (NPTs) for NPS as well as the increase in perceived quality of life in PwD and their caregivers . Consequently, the National Institute for Health and Care Excellence dementia guidelines recommend NPTs as first‐line treatments in the management of noncognitive behavioral disturbances in PwD.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Differently, systematic reviews have demonstrated the effectiveness of nonpharmacological treatments (NPTs) for NPS as well as the increase in perceived quality of life in PwD and their caregivers. 14,[18][19][20] Consequently, the National Institute for Health and Care Excellence dementia guidelines 21 focused on NPTs such as cognitive stimulation, pet therapy, doll therapy, and caregiver training in problem solving 18,22,23 to reduce NPS.…”
Section: Introductionmentioning
confidence: 99%